Diabetes-related amputations create considerable public health burden in the UK. (January 2018) - Graz, Heather; D'Souza, Vijay K.; Alderson, David E.C.; Graz, Michael
Highlights: Studies varied considerably in estimating costs involved in diabetic amputation. Inpatient care costs associated with diabetic amputation were £43.8 million. Post-amputation care annual expenditure was £20.8 million. Diabetes-related amputations create considerable public health and economic burden. Abstract: Aims: The main aim of this study was to assess the cost of diabetic amputation (both direct and indirect) to the National Health Service from the point of amputation onwards. Methods: This systematic review involved searches of published literature between January 2007 and March 2017 mainly using the bibliographic databases, the Cochrane Library, EMBASE via Ovid®, MEDLINE via Ovid®, as well as grey literature, both in print and in electronic formats published through non-commercial publications, which reported the cost of amputation due to diabetic foot ulcers. Results: The studies included in this review varied considerably in estimating the cost including cost elements and how those costs were categorised. The cost estimates for inpatient care associated with amputation involving admissions or procedures on amputation stumps in people with diabetes was £43.8 million. The annual expenditure for post-amputation care involving prosthetic care, physiotherapy, transport and wheelchair use was £20.8 million. Conclusions: There is a considerable public health and economic burden caused by diabetes-related amputations in England. More focussed research is needed with improved methods of estimating costs that would account for direct and indirect costs associated with diabetic amputation.